Saham Syariah di Pasar Modal Indonesia - Hikmah, Anur; Selasi, Dini (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
This study aims to explore the development, challenges, and opportunities of sharia stocks in Indonesia through a literature review method. Sharia stocks are part of the sharia capital market that is growing rapidly along with increasing public awareness of halal investment. This study examines literature from various academic sources, official reports, and related journals to provide a comprehensive understanding of sharia stocks in Indonesia. The results of the study indicate that sharia stocks have great potential in supporting the national economy, but challenges in the form of sharia financial literacy and limited access still need to be overcome.